Improved Lifetime Model of Energetic Electrons Due to Their Interactions With Chorus Waves - Dedong Wang; Yuri Y. Shprits; Bernhard Haas; Alexander Y. Drozdov (Geophysical Research Letters)
Abstract Chorus waves induce both electron acceleration and loss. In this letter, we provide significantly improved models of electron lifetime due to interactions with chorus waves. The new models fill the gap that previous models have on some magnetic local time (MLT) sectors of the Earth's magnetosphere. This improvement is critical for modeling studies. The lifetime models developed using two different methods are valid for electrons with an energy range from 1 keV to 2 MeV. To facilitate the integration of these new models into different ring current and radiation belt codes, we parameterize the electron lifetime as a function of L‐shell and electron kinetic energy at each MLT and geomagnetic activity (Kp). The parameterized electron lifetimes exhibit strong dependencies on L‐shell, MLT, and energy. Simulations using these new models demonstrate improved agreement with satellite observations compared to simulations using previous models, advancing our understanding of electron dynamics in the magnetosphere.